2021
DOI: 10.1177/15404153211042371
|View full text |Cite
|
Sign up to set email alerts
|

Moral Injury and Light Triad Traits: Anxiety and Depression in Health-Care Personnel During the Coronavirus-2019 Pandemic in Honduras

Abstract: The purpose of the current study was to determine the influence of moral injury and Light Triad (LT) personality traits on anxiety and depression symptoms of health-care personnel during the coronavirus-2019 pandemic. A quantitative, cross-sectional research design was used, the study included a sample of 169 health-care workers from Honduras. Data was gathered through the Moral Injury Symptom Scale for Health Professionals (MISS-HP), Light Triad Scale (LTS), the Generalized Anxiety Disorder-7, and the Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The 33 eligible studies were from 13 different countries, of which the US was the most frequent contributor in the number of studies ( k = 11) and the UK in enrolled HCWs number ( n = 14,815). 1 Six studies were from Asia, 12 from Europe, two from Latin America (Cooper-Bribiesca et al, 2023 ; Rodríguez et al, 2021 ), and one enrolled participants from several countries (Thomas et al, 2023 ). The 33 studies involved n = 31,849 participants (range of n = 33–12,965).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 33 eligible studies were from 13 different countries, of which the US was the most frequent contributor in the number of studies ( k = 11) and the UK in enrolled HCWs number ( n = 14,815). 1 Six studies were from Asia, 12 from Europe, two from Latin America (Cooper-Bribiesca et al, 2023 ; Rodríguez et al, 2021 ), and one enrolled participants from several countries (Thomas et al, 2023 ). The 33 studies involved n = 31,849 participants (range of n = 33–12,965).…”
Section: Resultsmentioning
confidence: 99%
“…MI imposes high emotional risks, as the individual can feel that their violations are beyond repair, resulting in shame, guilt, despair, and demoralisation (Jones, 2020 ; Litz et al, 2009 ). Evidence suggests that MI is associated with cognitive and behavioural alterations such as social withdrawal and suicidal behaviour, burnout, and with psychiatric disorders such as posttraumatic stress disorder (PTSD), depression, and anxiety (Bryan et al, 2018 ; Fani et al, 2021 ; Hall et al, 2022 ; Rodríguez et al, 2021 ; Testoni et al, 2022 ; Williamson et al, 2023 , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The PRISMA flowchart delineates the review process (see figure 1). Of the 81 full texts included in the review,6 12–21 43–112 some reported multiple studies in the same paper, so there were 88 separate studies included in the review. Of these, six reported prevalence estimates or average scores that could not be pooled, so they were included in the narrative synthesis only.…”
Section: Resultsmentioning
confidence: 99%
“…10 The MISS-HP contains a mix of positively and negatively worded items to reduce response bias, and it has a strong evidence base in the literature. [10][11][12][13][14] We stored responses in a secure REDCap® drive, accessible only to IRB-approved study members, to ensure anonymity.…”
Section: Methodsmentioning
confidence: 99%